Pedagogical Competence of Christian Teachers as Facilitators in the Process of Developing 21st Century Thinking Skills - Hutauruk, Kristian; Irawati, Wahyu (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
In the 21st century, national education required to reformulate its learning system to optimally meet the demands of students' thinking skills. However, assessments of Indonesian students' abilities in mathematics, science, literacy, and numeracy remained relatively low. To address this gap, students required teachers with strong pedagogical competence to help them improve their 21st-century thinking skills. This research aimed to examine the role of Christian teachers as facilitators in developing such skills. Their pedagogical responsibilities included guiding students toward learning that met student’s thinking needs, implementing problem-based learning, integrating technology in line with Christian values, and providing constructive feedback on students' thinking development. Christian teachers also needed to recognize sin as a human reality and understand the restoration of human's relationship with God through redemption, ensuring that educational practices remained untainted by secular postmodern philosophies. The author suggested that problem-based learning methods be explored to help students cultivate the thinking skills essential for the 21st century.